2012
DOI: 10.1016/j.bbmt.2012.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood as a Preferable Source of Stem Cells for Salvage Transplantation in Patients with Graft Failure after Cord Blood Transplantation: A Retrospective Analysis of the Registry Data of the Japanese Society for Hematopoietic Cell Transplantation

Abstract: To compare the different stem cell sources used in salvage transplantation for graft failure (GF) after cord blood transplantation (CBT), we retrospectively analyzed data of 220 patients who developed GF after undergoing CBT between January 2001 and December 2007 and underwent a second hematopoietic stem cell transplantation (HSCT) within 3 months. The donor sources for salvage HSCT were cord blood (n = 180), peripheral blood stem cells (PBSCs; n = 24), and bone marrow (BM; n = 16). The cumulative incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 18 publications
6
30
0
1
Order By: Relevance
“…A previous report including a small number of pediatric pGF patients showed an advantage of PBSC from mismatched related donors, 19 whereas our analysis demonstrated that CBT provided a survival rate similar to that of HSCT from mismatched related donors. The survival curve for CBT was superimposed on the curve for HSCT from a mismatched related donor, although engraftment achievement tended to be lower and engraftment was late.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…A previous report including a small number of pediatric pGF patients showed an advantage of PBSC from mismatched related donors, 19 whereas our analysis demonstrated that CBT provided a survival rate similar to that of HSCT from mismatched related donors. The survival curve for CBT was superimposed on the curve for HSCT from a mismatched related donor, although engraftment achievement tended to be lower and engraftment was late.…”
Section: Discussionsupporting
confidence: 43%
“…However, a recent study on engraftment probability of salvage CBT for pGF showed that a small fraction of children had a worse outcome than salvage HSCT from a mismatched related donor. 19 Another study on salvage CBT for pGF reported the association of cell dose of 42.5 Â 10 7 cells/kg with a better outcome. 13 In our cohort, the median TNC count of CB was 5.4 Â 10 7 cells/kg, which was considerably higher than that reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BM chimerism on day þ 30 of these cases showed a median of 100% of CB cells (range 75-100%). Median time to neutrophil engraftment in this group was 19 days (range [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Standard Engraftment Group (N ¼ 14)mentioning
confidence: 99%
“…[9][10][11] Outcome of patients who develop graft failure without a second transplantation is dismal with survival rates lower than 10%; 12 however, survival rates improve significantly to 30-60% after salvage transplantation using reduced intensity conditioning regimens. [13][14][15] From the extensive experience with CB transplantation, various risk factors have been associated with CB graft failure. [16][17][18] Once transplantation has been performed, early detection of graft failure is important to start rapid therapeutic measures such as immunomodulation and to launch a second transplant when appropriate as soon as possible.…”
Section: Introductionmentioning
confidence: 99%